2012
DOI: 10.4236/ojpsych.2012.24038
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of antidepressant therapy among patients with major depressive disorder

Abstract: Objective: Patients with major depressive disorder (MDD) often discontinue antidepressant therapy prematurely risking relapse, despite United Kingdom (UK) guidelines recommending therapy for up to at least six months after remission. More information is needed on the patterns of antidepressant discontinuation in UK primary care. Objectives of the study were to assess the patterns, incidence and predictors of therapy discontinuation among MDD patients initiating treatment with selective serotonin reuptake inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Patients' nonadherence to their psychotropic medication was associated with some non-modifiable demographic factors such as age and gender) [28]. In three studies, patients aged 60 years and older were more likely to be non-adherent to their medication [23,55,58]. Nevertheless, one study [60] reported that young age (less than 34 years) patients were also more likely to have medication non-adherence.…”
Section: Factors Related With Individual Behaviorsmentioning
confidence: 99%
“…Patients' nonadherence to their psychotropic medication was associated with some non-modifiable demographic factors such as age and gender) [28]. In three studies, patients aged 60 years and older were more likely to be non-adherent to their medication [23,55,58]. Nevertheless, one study [60] reported that young age (less than 34 years) patients were also more likely to have medication non-adherence.…”
Section: Factors Related With Individual Behaviorsmentioning
confidence: 99%
“…14 This study was designed after the original database queries that examined individual patient variation, however, the practicelevel data supplied by PCCIUR included an appropriate range of measures for analysis. The dataset was not restricted to treatment of individuals with a coded diagnosis of depression, as others have, 2,15 or to a depression-indicative Quality and Outcomes Framework (QOF) depression severity measure score. 15 As such, this study may be more broadly representative of individuals receiving antidepressant prescriptions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The dataset was not restricted to treatment of individuals with a coded diagnosis of depression, as others have, 2,15 or to a depression-indicative Quality and Outcomes Framework (QOF) depression severity measure score. 15 As such, this study may be more broadly representative of individuals receiving antidepressant prescriptions. For example, only 29% of patients in the current study had a depression diagnostic code recorded.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Although most clinical guidelines recommend antidepressants be continued for at least 6 months after symptom remission, 6 approximately one-third of patients discontinued the use of antidepressant medication within the first month of treatment, and about 40% quitted them by the sixth month of treatment. 7 Some patients may feel better and think they no longer need the medication, or stop their medicine because of bothersome side effects, without consulting their doctors. Premature withdrawal of treatment often led to increases relapse and recurrence rates, which were found to be high.…”
Section: Introductionmentioning
confidence: 99%